Decolonizing the Concept of Rule of Law in the Context of Cultural Diversity and Belt and Road Initiative - Sangroula, Yubaraj (Kathmandu School of Law Review, 2024)
It would not be unreasonable to argue that very little is left unsaid regarding the rule of law. Thousands of books and research works are published across the globe, arguing a multitude of theories and concepts in this regard. Academia worldwide has tiresomely grappled with defining the rule of law and establishing its conceptual framework, including the function’s scope, but without much success. Colonization of this concept by the Western scholarship is one of the serious problems faced by the essence of the rule of law. Western academia essentially connects the rule of law with liberal democracy as its motherly creator. It believes that rule of law walks in lockstep with liberal democracy; hence, it argues that no other than liberal democracy can nurture the rule of law. Due to this reason, in many, academia has been sharply divided between sections appreciating it as a boon to liberal democracy and suspecting its congenital relation with it. Certain scholars claim that the rule of law is an offspring of Western liberalism. However, some view that the rule of law and liberal democracy do not necessarily walk in lockstep. Certain critics have pointed out that the Western approach overlooks the cultural component of the rule of law. Going further ahead, they contend that the concept of the rule of law is often deceitfully used by Western democracy as an instrument of encouraging influence on those having different political systems. Consequently, the concept of the rule of law, particularly in its connotation presented by Western scholars, has faced many critics, comments, and views. As a result, it has become academically vague, functionally deluded, and politically dubious. This article intends to examine the contending arguments and cultural elements of the rule of law for promoting the approach of decolonizing the concept.